Regional specialisation as an endogenous factor in the development of Poland's provinces - Dorota Milek; Paulina Nowak (Institute of Economic Research (IER), 2015)
Regional and local development results from a complex interaction of many factors, including the development policy. Development priorities, contained in the strategic documents such as regional innovation strategies, emphasise building up the region's competitive advantage by identifying and developing regional specialisations. Regions need to identify their strengths and weaknesses and they have to rely strongly on innovation to develop. The aim of the paper is to undertake a diagnostic assessment of the specialisations of Poland's provinces, and also to validate that, in the context of the regional innovation policy, on the example of the swietokrzyskie province. The paper employs the Krugman dissimilarity index, which is computed on the basis of a comparison of a given region's economic structure with average structure of other regions.
Keywords: A11; B16; 330; economic development of the country; regional innovation policy; regional specialisation; Krugman index